A novel green synthesis approach for shape memory polymer nanocomposites decorated with silver nanoparticles - Selcuk Pekdemir, Sibel; Karagulle, Burcu; Pekdemir, Mustafa Ersin; Tas, Recep; Aksoy, Edanur; Aydin, Derya (Wiley, 2023)
A new, low-cost, and direct green synthesis strategy was developed for the preparation of polymer composites composed of silver nanoparticles (AgNPs) decorated on a shape memory polymer blend using Rubus caesius L. leaves. X-ray powder diffraction, ultraviolet-visible spectroscopy (UV-vis), scanning electron microscopy, and energy dispersive X-ray spectroscopy (EDS) elemental composition were applied to characterize the crystal size, morphology, and elemental composition of Ag-NPs. UV-vis spectra detected the characteristic absorbance signal of AgNPs at about 430 nm, and the average crystal size of nanoparticles was calculated as about 12.60 nm. When nanocomposite films were characterized by attenuated total reflectance infrared spectroscopy, characteristic polylactic acid, and poly ethylene glycol (PEG) signals were determined. From the thermogravimetric analysis curves, it was determined that the amount of residue of nanocomposites increased as the amount of AgNP increased. It was seen that AgNPs did not affect the Tg temperature of the nanocomposite films, while it was also a proof that the polymer blend was immiscible. It was observed that the shape recovery properties of nanocomposite films were better with increasing AgNPs content. Finally, both green synthesized AgNPs and nanocomposites prepared with shape memory polymers showed very good antibacterial activity against Gram-positive and Gram-negative bacteria.HighlightsGreen synthesis of silver nanoparticles (AgNPs) was carried out with Rubus caesius L. leaves.The synthesized AgNPs were characterized by ultraviolet visible spectroscopy and x-ray powder diffraction.Composite films were prepared with poly lactic acid/poly e-caprolactone blend by solvent casting method.The amount of residue of nanocomposites increased with increasing AgNPs percentage.The nanocomposite film containing 10% AgNPs has good activity. PLA-PEG blend / AgNPs nanocompositesimage
Keywords: antibacterial; green synthesis silver nanoparticles; nanocomposite; poly e-caprolactone; poly lactic acid; shape memory effect